Hypovitaminosis D as a risk factor for severe autism spectrum disorder - Diyah Rakanita Undang; Mei Neni Sitaresmi; Roni Naning (Paediatrica Indonesiana, 2021)
Background Vitamin D is an important risk factor for autism spectrum disorder (ASD). However, research on hypovitaminosis D as a risk factor for severe ASD has been limited. To our knowledge, no such studies have been done in Indonesia. Objective To evaluate hypovitaminosis D as a risk factor for severe ASD. Methods This cross-sectional study included children aged 2-18 years who fulfilled the ASD DSM-5 diagnostic criteria. Subjects were consecutively sampled from April - June 2019 at the Child Growth and Polyclinic, Dr. Sardjito General Hospital, Yogyakarta. Assessment of ASD severity was carried out using the Childhood Autism Rating Scale Second Edition (CARS-2) questionnaire. Serum 25(OH)D examination was done in the Clinical Laboratory, Dr. Sardjito General Hospital. Results Of 36 children with ASD, 36.1% had hypovitaminosis D (<30 ng/mL) and 69.4% had severe ASD, based on the CARS-2 questionnaire (≥37-60). Bivariate analysis revealed that children with hypovitaminosis D had more severe CARS-2 values ​​(92.3%) compared to those with normal vitamin D levels (56.5%) (PR 1.633; 95%CI 1.10 to 2.42; P=0.031). Multivariate analysis with logistic regression revealed that hypovitaminosis D increased the risk of severe ASD (PR 1.65; 95%CI 1.06 to 2.56; P=0.037). However, other variables such as gender, parental education, attention deficit and hyperactivity disorder (ADHD), epilepsy, sleep disorders, pharmacotherapy and non-pharmacotherapy had no significant relationships with severe ASD. Conclusion Children with ASD and hypovitaminosis D have a 1.65 times higher risk of severe ASD compared to children with ASD and sufficient vitamin D levels. We recommend that children with ASD undergo serum 25(OH)D monitoring.